Prognostic peripheral blood biomarkers at ICU admission predict COVID-19 clinical outcomes - Messing, Melina; Sekhon, Mypinder S.; Hughes, Michael R.; Stukas, Sophie; Hoiland, Ryan L.; Cooper, Jennifer; Ahmed, Nyra; Hamer, Mark S.; Li, Yicong; Shin, Samuel B.; Tung, Lin Wei; Wellington, Cheryl L.; et al. (Frontiers in Immunology, 2022)
The COVID-19 pandemic continues to challenge the capacities of hospital ICUs which currently lack the ability to identify prospectively those patients who may require extended management. In this study of 90 ICU COVID-19 patients, we evaluated serum levels of four cytokines (IL-1β, IL-6, IL-10 and TNFα) as well as standard clinical and laboratory measurements. On 42 of these patients (binned into Initial and Replication Cohorts), we further performed CyTOF-based deep immunophenotyping of peripheral blood mononuclear cells with a panel of 38 antibodies. All measurements and patient samples were taken at time of ICU admission and retrospectively linked to patient clinical outcomes through statistical approaches. These analyses resulted in the definition of a new measure of patient clinical outcome: patients who will recover after short ICU stays (< 6 days) and those who will subsequently die or recover after long ICU stays (> 6 days). Based on these clinical outcome categories, we identified blood prognostic biomarkers that, at time of ICU admission, prospectively distinguish, with 91% sensitivity and 91% specificity (positive likelihood ratio 10.1), patients in the two clinical outcome groups. This is achieved through a tiered evaluation of serum IL-10 and targeted immunophenotyping of monocyte subsets, specifically, CD11clow classical monocytes. Immunophenotyping revealed clear predictors of clinical outcome in COVID-19 providing a highly sensitive and specific prognostic test that could prove useful in guiding clinical resource allocation.